Impacto da restrição alimentar sobre os parâmetros biometricos, hormonais e metábolicos de ovinos Santa Inês - Branco, Karoliny Farias Castelo (2015)
The present study aimed to evaluate biometric measurements and blood and hormonal parameters of Santa Ines lambs. Thirty lambs with an average live weight of 13.0 ± 1.49 kg and 60 days of age were used to estimate glucose, cholesterol, β-hydroxybutyrate, urea N, total protein, albumin, globulin, chloride, calcium, phosphorus, magnesium, and leptin, insulin, and thyroxine (T4) hormones. Lambs were assigned to a randomized complete design in a 3 × 2 factorial arrangement consisting of three levels of food restriction (FR) (control, 30%, and 60%), three collection periods corresponding the age of the animals (14, 18, and 23 weeks of age), and two sex categories (castrated and uncastrated). Blood was collected by jugular venipuncture in the three collection periods. For biometric measurements, a randomized complete design in a 3 × 2 factorial arrangement was adopted, taking into account restriction levels and sex categories. Measurements were taken every two weeks throughout the experimental period. The hormone thyroxine was not influenced by age, diet, or sex category. Leptin and insulin increased with the animal age (P <0.01). Glucose concentrations decreased as the FR level were increased (P <0.001). β-hydroxybutyrate concentrations increased as the food restriction was increased (P <0.001). Urea nitrogen was influenced by age and experimental diet (P <0.001), and there was an age × sex category interaction effect (P <0.01). Concentrations of total cholesterol and total proteins were not influenced by experimental treatments (P <0.05), but albumin and globulin were influenced by age (P <0.001, P <0.01). Plasma concentrations of chloride, calcium, magnesium, and phosphorus varied significantly according to age. Animals subjected to FR grew at a slower rate, and the negative influence was more pronounced at 60% FR. At 30% FR, the growth rate decline was more noticeable at 100 days of age for body weight (BW); at 130 days for body condition score (BCS) and chest girth (CG); at 145 days for rump height (RH); and at 160 days for rump length (RL) and breast width (BW). Pearson's correlation analysis showed biometric measurements are co-dependent on the feeding level because correlations were high and significant in control animals (r = 0.61 to 0.95). It is concluded that the metabolic parameters were more influenced by age than by diet, and food restriction affects the metabolic and hormonal profiles, in particular β-hydroxybutyrate and insulin. Body condition score, body weight, and breast width were the most significantly affected by FR parameters.